Dislocation micromechanisms under single slip conditions - Veyssière, Patrick; Chiu, Yu-Lung; Niewczas, Marek (International journal of materials research, 2022)
The microstructures formed in the early stage of deformation of Cu, Al, and TiAl in single slip and at low temperatures are analysed. While dislocations are highly mobile in Cu and Al, they are subject to a significant lattice friction in TiAl. Also, they are dissociated over a few nm in Cu, not in Al and TiAl. These various properties are manifested in the self-organization of dislocations in bundles. The role of nanometric prismatic loops in producing specific debris is emphasized in the context of the so-called collinear interaction. Possible artefacts arising from microstructural relaxation after unloading are discussed and limitations of weak-beam analyses assessed.